2016
DOI: 10.1007/s10646-016-1680-4
|View full text |Cite
|
Sign up to set email alerts
|

Unintended effects of the herbicides 2,4-D and dicamba on lady beetles

Abstract: Weed resistance to glyphosate and development of new GM crops tolerant to 2,4-dichlorophenoxyacetic acid (2,4-D) and dicamba is expected to lead to increased use of these herbicides in cropland. The lady beetle, Coleomegilla maculata is an important beneficial insect in cropland that is commonly used as an indicator species in safety evaluations of pesticides. Here, we examined the lethal and non-lethal effects of 2,4-D and dicamba active ingredients and commercial formulations to this lady beetle species, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…For example Hill et al [51] reported that the recommended concentration of a commercially formulated 2,4-D caused up to 80% mortality in the mirid, Ecritotarsus catarinensis (Carvalho) (Hemiptera: Miridae) after the insect was exposed for 72 hours. In addition, Freydier and Lundgren [14] reported 80% mortality in ladybug, Coleomegilla maculata De Geer (Coleoptera: Coccinelidae) larvae due to exposure to 2,4-D. Furthermore, Adam [52] reported four times mortality in three species of coccinelid beetle larvae, Coccinella transversoguttata (Fald.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…For example Hill et al [51] reported that the recommended concentration of a commercially formulated 2,4-D caused up to 80% mortality in the mirid, Ecritotarsus catarinensis (Carvalho) (Hemiptera: Miridae) after the insect was exposed for 72 hours. In addition, Freydier and Lundgren [14] reported 80% mortality in ladybug, Coleomegilla maculata De Geer (Coleoptera: Coccinelidae) larvae due to exposure to 2,4-D. Furthermore, Adam [52] reported four times mortality in three species of coccinelid beetle larvae, Coccinella transversoguttata (Fald.…”
Section: Plos Onementioning
confidence: 99%
“…Atrazine works by inhibiting photosynthesis by blocking electron transfer at the reducing site (plastoquinone binding site) of photosynthesis complex II in the chloroplasts in higher plants [10,11]. Although 2,4-D and atrazine based herbicides are among the most commonly used herbicides in many parts of the world (including Nigeria) due to its low cost, selectivity, efficacy and broad spectrum, their negative effects on beneficial and none target organisms are well documented in the literature [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples include the lower fecundity of the pea aphid (Acyrthosiphon pisum) exposed to sublethal concentrations of Margosan-O extracts (active ingredient, azadirachtin) [66] and that of the cotton aphid (Aphis gossypii) exposed to cycloxaprid [67], both of which can help reduce the populations of those pests and achieve their effective long-term control. However, similar negative effects can be observed in beneficial, predatory and parasitoid arthropod species, such as the decrease in fecundity of predatory Coleomegilla maculata lady beetles after exposure to commercial formulations of 2,4-D and dicamba herbicides [68] and reduced ovipositions of Eriopis connexa lady beetles exposed to the insecticides teflubenzuron and cypermethrin [69]; the severe reduction in fecundity of predatory thrips (Scolothrips longicornis) exposed to abamectin [70]; or the reduced fecundity of the generalist predatory bug Orius armatus exposed to spinosad [71], amongst many others. Other non-target organisms also experience impaired reproductive effects; for example, the reduced fecundity of queen honey bees (Apis mellifera) exposed to sublethal doses of bifenthrin and deltamethrin [72] or to field relevant residues of imidacloprid [73,74]; the reduced spawning of Australian crimson-spotted rainbowfish (Melanotaenia fluviatilis) and medaka fish (Oryzias latipes) exposed to sublethal concentrations of esfenvalerate insecticide in water [75,76]; or the reduced population growth rate of Daphnia spp.…”
Section: Toxicity Assessmentmentioning
confidence: 82%
“…Sometimes, herbicides have indirect effects on the phytophagous beneficial insects through destruction of their habitat or reduction of the nutritional value of their host plants [21][22][23]. Herbicides also have lethal and sublethal effects on ladybird beetles [24], green lacewings [25], earthworms [26], parasitic wasps, and honeybees [27] when they come into direct contact with herbicides either topically or through ingesting treated food materials. Furthermore, application of the same herbicide frequently over the years may produce herbicide-resistant weeds [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%